2019
DOI: 10.3389/fpsyg.2019.02319
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between People’s Environmental Considerations and Pro-environmental Behavior in Lithuania

Abstract: Given the need for global action on climate change, it is crucial to comprehend which factors motivate people in different countries to act more pro-environmentally. Lithuania is a post-socialist country that has recently increased commitment to foster pro-environmental behavior of individuals, by implementing interventions that target mainly the personal costs and benefits of relevant behaviors. Yet, research suggests that people’s general environmental considerations, namely biospheric values and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 66 publications
8
49
0
2
Order By: Relevance
“…Our findings in fact indicate that adolescents have rather strong biospheric values. At the same time, a comparison with a recent study in Lithuania with adults (Balundë et al, 2019; Supplementary Material 4) reveals that biospheric and altruistic values of adolescents in the current study were slightly weaker and egoistic values were slightly stronger compared to adults; for hedonic values there was no such consistent pattern. These results are in line with previous evidence that biospheric values may be weaker in adolescence than later in life (Schwartz, 2012b;Vecchione et al, 2019).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Our findings in fact indicate that adolescents have rather strong biospheric values. At the same time, a comparison with a recent study in Lithuania with adults (Balundë et al, 2019; Supplementary Material 4) reveals that biospheric and altruistic values of adolescents in the current study were slightly weaker and egoistic values were slightly stronger compared to adults; for hedonic values there was no such consistent pattern. These results are in line with previous evidence that biospheric values may be weaker in adolescence than later in life (Schwartz, 2012b;Vecchione et al, 2019).…”
Section: Discussionsupporting
confidence: 47%
“…Particularly people's strong biospheric values have been found to be important to explain multiple pro-environmental behaviors (de Groot and Steg, 2007a,b;Steg et al, 2012Steg et al, , 2014Merrill et al, 2018). Studies found positive relationships between biospheric values and recycling and environmental activism (Balundë et al, 2019), energy conservation (de Groot et al, 2012;Sahin, 2013) and acceptability of policies to reduce car use (Hiratsuka et al, 2018;Ünal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The finding echoes the idea that motivation drives individuals towards performing targeted actions [79][80][81]. The results of the current study corroborated earlier studies which demonstrate significant positive effects of different types of motivation and environmental behaviors including climate conserving behaviors [50,[79][80][81][83][84][85][86]. This nature of the Malaysian secondary curriculum explains the considerable large effect size of motivation.…”
Section: Discussionsupporting
confidence: 90%
“…Pongiglione [83] identified barriers for the lacking motivation for adopting pro-environmental behaviors among adults. The studies discussed above indicate that motivation as the antecedent for developing pro-environmental behaviors [84,85]. Motivation is also integral for adopting climate conserving behaviors.…”
Section: Motivation and Climate Conserving Behaviormentioning
confidence: 99%
“…Research on pro-environmental behavior receives ever-increasing interest from researchers worldwide and has led to a vast body of research of predictive models of pro-environmental behavior. The research ranges from models designed specifically for investigating pro-environmental behaviors, such as the Value-Belief-Norm theory [6][7][8][9][10], the Value-Identity-Personal norm model [11,12] (to name a few), and the use of general models of explaining behavior such as the Theory of Planned Behavior (TPB) [6,13,14]. The knowledge gained through research thus far has focused on how the aforementioned models function in general and their general utility in explaining behavior.…”
Section: Introductionmentioning
confidence: 99%